Managing Violence: In-Prison Behavior Associated with Placement in an Alternative Disciplinary Segregation Program - Meyers, Travis J. (American journal of criminal justice, 2023)
The use of segregation continues to be at the forefront of debates on the most effective way to address violence in prisons. Concern over the negative impact of these placements has prompted correctional administrators to employ alternative strategies to reduce their segregated populations and address serious misconduct. Few studies, however, have explored the impact that these strategies have on future behavioral outcomes. To address this gap, the current study explores the effectiveness of a disciplinary segregation program reserved for those who engage in violent misconduct during their incarceration. This study employs a quasi-experimental research design to estimate the treatment effects of placement in a disciplinary segregation program on subsequent levels of institutional misconduct during a one-year follow-up. Results from this study reveal that placement in the disciplinary segregation program had no effect on subsequent levels of serious in-prison misconduct amongst participants when compared to their matched counterparts. Our findings suggest that scholars and practitioners should work to build a response to in-prison violence that starts with what is known about the causes of violence and what effectively modifies attitudes and behaviors. Future research should include rigorous measures of both program process and implementation to better identify effective forms of intervention.